Actual versus recommended storage temperatures of oral anticancer medicines at patients' homes. (March 2019) - Vlieland, ND; van den Bemt, BJF; van Riet-Nales, DA; Bouvy, ML; Egberts, ACG; Gardarsdottir, H
Background: Substantial quantities of unused medicines are returned by patients to the pharmacy each year. Redispensing these medicines would reduce medicinal waste and health care costs. However, it is not known if medicines are stored by patients as recommended in the product label. Inadequate storage may negatively affect the medicine and reduce clinical efficacy whilst increasing the risk for side effects. Objective: To investigate the proportion of patients storing oral anticancer medicines according to the temperature instructions in the product label. Methods: Consenting adult patients from six Dutch outpatient hospital pharmacies were included in this study if they used an oral anticancer medicine during February 2014 – January 2015. Home storage temperatures were assessed by inclusion of a temperature logger in the original cancer medicines packaging. The primary outcome was the proportion of patients storing oral anticancer medicines as specified in the Summary of Product Characteristics, either by recalculating the observed temperature fluctuations to a single mean kinetic temperature or by following the temperature instructions taking into account a consecutive 24-h tolerance period. Results: Ninety (81.1%) of the 111 included patients (47.8% female, mean age 65.2 (SD: 11.1)) returned their temperature loggers to the pharmacy. None of the patients stored oral anticancer medicines at a mean kinetic temperature above 25℃, one patient stored a medicine requiring storage below 25℃ longer than 24 h above 25℃. None of the patients using medicines requiring storage below 30℃ kept their medicine above 30℃ for a consecutive period of 24 h or longer. Conclusion: The majority of patients using oral anticancer medicines store their medicines according to the temperature requirements on the product label claim. Based on our results, most oral anticancer medicines will not be negatively affected by temperature conditions at patients' homes for a maximum of three months and are likely to be suitable for redispensing.